STUDI PANGSA PASAR PADA SISTEM ANGKUTAN ANTAR KOTA ANTAR PROPINSI PERUM DAMRI (STUDI KASUS : TRAYEK PURWOKERTO-JAKARTA DENGAN PELAYANAN CEPAT TERBATAS) - (NIM 28097007), SUCIPTO
Abstract : The number of inter city inter province public transport bus companies that operate on their fleet between Purwokerto and Jakarta cause a firm competition to fight the market share even less with economy crisis continuously in which the operation cost increased while the revenue relative down, so many companies defend to survive only. Certainly each company wants to still survive even to increase. As service company, service is fact even to get the market share, Perum DAMRI Purwokerto Station up to now has already carried on extend better service with raised level of service. In order to be able to be identified exactly what service variables that influence greatly to get market share, so must be carried out the action of sharing user preference to evaluate service variables, to decide mode choice. By classifying mode into Perum DAMRI and non DAMRI, the identification of service variables which influence in selecting mode is grouped into qualitative variable and quantitative variable which is obtained by survey. The level of monitoring based on aggregate information and individual behavior that involve directly in mode choice process. Then it is calculated by using Biner model, it is obtained mathematics model as follows : PD = I/(1+e-(-8.844145-0.0035388701-30.541459W1+4.60067x1+ 4.421976X2 +5.069195x3-2.9416363X4 -1.4659591X6 +3.0652454X7 + 4.1378109X8 + 3.0805350x12)) Which P(D)) is probability choice of mode DAMRI, 01: bus ticket fare Purwokerto - Jakarta, 02 : transport cost from the last station to the destination, W1 : waiting time in station, W2 : time service Purwokerto - Jakarta, X1 : time accuracy of bus departure, X2 : schedule suitability of bus departure X3 : transportation frequency , X4 : risk of lost/damaged goods X6 : level of noise, vibration, shake in bus, seat allowance, room cleanliness X12 : ticket discount directly and indirectly.